2012
DOI: 10.1177/230949901202000308
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Nailing Supplemented with Poller Screws for Proximal Tibial Fractures

Abstract: Poller screws help maintain fixation of intramedullary nailing and alignment of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…With the development of IMN design and adjunctively surgical techniques, surgeons began to apply these methods, like angle‐stable and multi‐directional distal screw or blocking screw in distal tibia fractures to maintain reduction, alignment and prevent malunion. A multi‐center pilot study conducted by Höntzsch showed that this technique help improve the stability in axial and torsional loading, which is statically and dynamically higher than conventional IMN.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of IMN design and adjunctively surgical techniques, surgeons began to apply these methods, like angle‐stable and multi‐directional distal screw or blocking screw in distal tibia fractures to maintain reduction, alignment and prevent malunion. A multi‐center pilot study conducted by Höntzsch showed that this technique help improve the stability in axial and torsional loading, which is statically and dynamically higher than conventional IMN.…”
Section: Discussionmentioning
confidence: 99%
“…Krettek et al [ 4 ] reported that with the use of Poller screws (blocking screws) with small-diameter IM nails in metaphyseal tibial fractures for supplemental stability, the mean loss of reduction was 0.5° in the frontal plane and 0.4° in the sagittal plane. Similarly, various authors have described the use of interlocking intramedullary nail in combination with blocking screws in metaphysis of long bones to improve reduction, prevent secondary displacement, and to augment and maintain the alignment and stability [ 10 14 ]. The use of blocking screws has also been reported to hasten the bone healing in fractures [ 15 ] and nonunions [ 16 ] as well as to reduce the risk of implant failure [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blocking screws are designed to guide the intramedullary nail to the desired direction by narrowing the intramedullary canal and obtaining better reduction [ 18 , 19 ]. In our cases, we inserted a 2.4 mm K-wire into the fragment from lateral to medial to prevent a hyperextension deformity and guided the intramedullary nail using the Poller screw technique.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve anatomical reduction of supracondylar fractures, in 1999 Krettek et al [ 16 , 17 ] reported the Poller (blocking) screw technique as an important adjunct for intramedullary nailing. This technique has subsequently been shown to be effective in aiding fracture reduction [ 18 , 19 ], but there have been no reports of this technique being applied specifically for the reduction of periprosthetic supracondylar fracture. Here we report 2 cases of such fracture treated with intramedullary nailing and the blocking screw technique that achieved excellent reduction.…”
Section: Introductionmentioning
confidence: 99%